Sinr Analysis in a Tunnel Using Multiple Vlc Cells with Tdma - Soto-Gomez, J; Estela-Zamora, M (Institute of Electrical and Electronics Engineers Inc., 2020)
In this paper, intercell interference (ICI) produced by adjacent/neighboring cells in a user who moves through a mining tunnel is studied. For this, a visible light communication (VLC) system is modeled that uses Time Division Multiplexing access(TDMA) and two possible topologies of LED distribution are presented within a mining tunnel to be analysed. The interference of an optical cell in its neighboring cells is analysed and compared in detail, as well as the signal to interference plus noise ratio (SINR) for different paths within the tunnel. © 2020 IEEE.